c-Abl regulates gastrointestinal muscularis propria homeostasis via ERKs - Jinnan Xiang (Nature Portfolio, 2017)
Abstract The gastrointestinal tract is responsible for food digestion and absorption. The muscularis propria propels the foodstuff through the GI tract and defects in intestine motility may cause obstruction disorders. Our present genetic studies identified non-receptor tyrosine kinase c-Abl as an important regulator of the muscularis propria homeostasis and a risk factor for rectal prolapse. Mouse deficient for c-Abl showed defects in the muscularis propria of gastrointestinal tract and older c-Abl −/− mice developed megaesophagus and rectal prolapse. Inhibition of c-Abl with imatinib mesylate, an anti-CML drug, or ablation of c-Abl using Prx1-Cre, which marks smooth muscle cells, recapitulated most of the muscularis propria phenotypes. The pathogenesis of rectal prolapse was attributable to overproliferation of smooth muscle cells, which was caused by enhanced ERK1/2 activation. Administration of ERK inhibitor U0126 impeded the development of rectal prolapse in c-Abl deficient mice. These results reveal a role for c-Abl-regulated smooth muscle proliferation in the pathogenesis of rectal prolapse, and imply that long-term use of imatinib mesylate may cause gastrointestinal problems in patients while ERK inhibitor may be effective in treating rectal prolapse.